Health beliefs and breast self-examination among undergraduate female students in public universities in Klang Valley, Malaysia - Akhtari-Zavare, Mehrnoosh; Juni, Muhamad Hanafiah; Ismail, Irmi Zarina; Md Said, Salmiah; Abd Latiff, Latiffah (Asian Pacific Organization for Cancer Prevention, 2015)
Background: Breast cancer is the most frequently occurring cancer in women and the most common cause of cancer death worldwide. Materials and Methods: A cross-sectional study was carried out among 792 female undergraduate students in public universities in Klang Valley, Malaysia, from January to April 2011. Data were collected using a validated questionnaire developed for this study. Results: The mean age of respondents was 21.7±1.2 years. Most of them were single (96.8%), Malay (91.9%) and 150 (19.6%) claimed they had practiced BSE. There was a significant differences between performers and non-performers correlated to age, marital status, check breast by doctor, and being trained about BSE. Performers had lower mean scores for perceived barriers and susceptibility and higher mean score for confidence. Stepwise logistic regression analysis yielded four significant predictor variables. Conclusions: Overall our findings indicate that the practice of BSE while perceived as being important is not frequently practiced among female in Malaysia. Targeted education should be implemented to improve early detection of breast cancer.